IMPLEMENTATION OF CONTAINER ORCHESTRATOR MANAGEMENT IN LEARNING MANAGEMENT SYSTEM - Subhi Basit, Muhamad; Pratama, Arif; Firizqi, Januponsa Dio; Indrajit, Richardus Eko (Informatika, Universitas Jenderal Soedirman, 2023)
The pandemic that started in 2019 made technology even more important. Accelerating digital adaptation and transformation in the education sector, namely the Learning Management System (LMS) is very helpful in the teaching and learning process. Various LMS platforms are widely used and developed by various agencies. Pradita University is also developing an LMS which is made with the node.js programming language and the next.js framework which can be accessed on the pradita.digital site. The choice of using the wrong technology can cause the problematic LMS that is used to become slow and heavy, to the point where it cannot be accessed. The use of technology with the hypervisior concept which was previously commonly used has various weaknesses. For this reason, the Pradita LMS was developed using container orchestrator technology and Rancher Kubernetes as container orchestrator management. By utilizing Rancher as a container orchestrator management, it can make it easier to use with a user friendly GUI. In this study aims to prove that the use of Rancher in improving the quality and performance of LMS Pradita. Among them by identifying system efficiency, providing better scalability, increasing the availability of Pradita LMS, Rancher is able to manage applications and containers used for Pradita LMS, and saving costs used in implementing physical devices. By using the experimental method applied in this study, the results of system efficiency testing and scalability testing carried out with a load of up to 200 users can run properly and efficiently, then the availability test proves that the LMS is still available even when there are workers who are not operating, and testing rancher management capabilities lead to conclusions Rancher runs optimally and uses resources efficiently in accordance with the objectives in this study.